The magnitude of the exercise pressor reflex is influenced by the active skeletal muscle mass in the decerebrate rat - Estrada, Juan A. (Am J Physiol Regul Integr Comp Physiol, 2020)
The exercise pressor reflex is composed of two components, namely the muscle mechanoreflex and the muscle metaboreflex. The afferents evoking the two components are either thinly myelinated (group III) or unmyelinated (group IV); in combination they are termed “thin fiber afferents.” The exercise pressor reflex is often studied in unanesthetized, decerebrate rats. However, the relationship between the magnitude of this reflex and the number of thin fiber afferents stimulated by muscle contraction is unknown. This lack of knowledge prompted us to test the hypothesis that the magnitude of the exercise pressor reflex was directly proportional to the amount of muscle mass activated. Muscle mechanoreceptors were stimulated by stretching the calcaneal tendon. Likewise, muscle metaboreceptors were stimulated by injecting lactic acid into the arterial supply of the hindlimb muscles. In addition, both muscle mechanoreceptors and metaboreceptors were stimulated by statically contracting the hindlimb muscles. We found that simultaneous bilateral (both hindlimbs) stimulation of thin fiber afferents with stretch, lactic acid, and static contraction evoked significantly greater pressor responses than did unilateral (one hindlimb) stimulation of these afferents. In addition, the magnitude of the pressor responses to bilateral simultaneous stimulation of thin fiber afferents evoked by stretch, lactic acid, and contraction was not significantly different from the magnitude of the sum of the pressor responses evoked by unilateral stimulation of these afferents by stretch, lactic acid, and contraction. We conclude that the magnitude of the exercise pressor reflex and its two components is dependent on the number of afferents stimulated.